Assessing diets of 3-year-old children: evaluation of an FFQ. Issue 5 (1st May 2013) - Jarman, Megan; Fisk, Catherine M; Ntani, Georgia; Crozier, Sarah R; Godfrey, Keith M; Inskip, Hazel M; Cooper, Cyrus; Robinson, Sian M; the Southampton Women's Survey Study Group
Abstract Objective To evaluate the use of an administered eighty-item FFQ to assess nutrient intake and diet quality in 3-year-old children. Design Frequency of consumption and portion size of the foods listed on the FFQ during the 3 months preceding the interview were reported by the child's main caregiver; after the interview a 2 d prospective food diary (FD) was completed on behalf of the child. Nutrient intakes from the FFQ and FD were estimated using UK food composition data. Diet quality was assessed from the FFQ and FD according to the child's scores for a principal component analysis-defined dietary pattern ('prudent' pattern), characterised by high consumption of fruit, vegetables, water and wholemeal cereals. Setting Southampton, UK. Subjects Children (n 892) aged 3 years in the Southampton Women's Survey. Results Intakes of all nutrients assessed by the FFQ were higher than FD estimates, but there was reasonable agreement in terms of ranking of children (range of Spearman rank correlations for energy-adjusted nutrient intakes, rs = 0·41 to 0·59). Prudent diet scores estimated from the FFQ and FD were highly correlated (r = 0·72). Some family and child characteristics appeared to influence the ability of the FFQ to rank children, most notably the number of child's meals eaten away from home. Conclusions The FFQ provides useful information to allow ranking of children at this age with respect to nutrient intake and quality of diet, but may overestimate absolute intakes. Dietary studies of young children need to consider family and child characteristics that may impact on reporting error associated with an FFQ.